Clinical Outcomes of Implementing Guideline for Alcohol Use Disorder in Service Plan at Mahasarakham Province - Anekwit, Natwarat (Journal of the Psychiatric Association of Thailand, 2018)
Objectives : To evaluate service accessibility rate and clinical outcomes of patients with alcohol use disorder before and after implementing the clinical guideline in service plan of Mahasarakham province. Methods : This was an analytic study aimed to compare accessibility rate and clinical outcomes before and after implementing clinical practice guideline for patients with alcohol use disorder in service plan of Mahasarakham province (CPG-AWS). The participants were patients aged above 15 years old diagnosed with F10.1-F10.5 by ICD-10 criteria and had alcohol withdrawal symptoms. Data were collected by clinical record forms and medical records from the twelve district hospitals under the service plan of Mahasarakham province between October 1st, 2013 and January 31st, 2018. Data analysis was done by using descriptive statistics, Odds ratio and Chi-square. Results : After clinical guideline implementation, total number of patients with alcohol use disorder was 3,610 with male preponderance (95.43%). 40.89% of those patients were diagnosed with alcohol dependence (F10.2). Service accessibility rate of patients with F10.2 diagnosis increased significantly from 5.40% to 35.10% (p < 0.01). Percentage of referral patients with delirium tremens also decreased significantly from 0.50% to 0.10% (p = 0.02). There were 108 patients (2.99%) with sustained full remission after 1 year. No death case reported after using the guidelinet. Conclusion : Implementation of the clinical guideline in service plan of Mahasarakham province for patients with alcohol drinking behaviors increased the service accessibility rate and the clinical outcomes was correspondingly improved.